JAEPL, Vol. 6, Winter 2000-2001 - Joonna S. Trapp; Bradley T. Peters (Journal of the Assembly for Expanded Perspectives on Learning, 2000)
Essays Mary Ann Cain. New Locations for Discursive Agency: The Story of Anandamai Ma. This paper aims to relocate our relationship to modes of knowledge that fall outside of Western rationalism and conceptual thought by relocating our understanding of agency through the figure of Anandamai Ma, a 20th century Hindu "saint. Mark Smith. The Widening Gyre: Images as Central to the Global Village. The image is emerging as the lingua franca of technological culture, both resurrecting characteristics of pre-literate classicism and consolidating the global community. Lynn Briggs, Fred Schunter, and Ray Melvin. In the Name of the Spirit. The authors argue that naming experiences "spiritual" is important to an expanded understanding of goals, struggles, and success in their writing center practice. Gwen Gorzelsky. Writing Awareness. The author argues that, by practicing embodied, metaphoric ethnography, educators can revise their roles in classroom social systems and so pursue the goals of critical pedagogy. Kathleen Welch. A Medical Humanities Course: A Pertinent Pause on the Medical Beat. This article summarizes the findings of one ethnographic study and demonstrates that, by emphasizing self- reflection and discussion, an interdisciplinary literature and medicine course provides medical students a brief but important, time for retrospection. Phyllis Whitin. Inventing Metaphors to Understand the Genre of Poetry. To make personally meaningful connections with poetry as a genre, students in the author's seventh grade classes generated original metaphors to describe the essence of poetry. William C. Johnson. Remembering Things We've Never Done: Memory's Daughters and the Literary Experience. Memory, essential in creative writing, inspires us to weave literary reading into the narrative of personal experience and to seek, through recollection, our psychic wholeness. Reviews Sandi Alberston-Shea. Letters for the Living: Teaching Writing in a Violent Age. (Michael Blitz and C. Mark Huribert, 1999). Susan A. Schiller. Education and the Soul: Toward a Spiritual Curriculum. (John P. Miller, 2000). Jeffrey D. Wilhelm. Radical Presence: Teaching as Contemplative Practice. (Mary Rose O'Reilly, 1998).